2019
DOI: 10.3390/separations6030042
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Relative Retention of Polar Stationary Phases in Hydrophilic Interaction Chromatography

Abstract: A large number of polar stationary phases with diverse chemistry have been developed for various applications in hydrophilic interaction chromatography (HILIC). However, column manufacturers employ different testing procedures to evaluate retention of the polar stationary phases. This renders the retention data impossible for comparison and makes it difficult for the users to select the right stationary phase based on retention. We have evaluated 25 polar stationary phases using cytosine and uracil as the mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This is the case, for instance, of inorganic salts in RPLC. In HILIC these salts cannot be used because of its strong polarity and several studies propose toluene as hold-up volume marker due to its non-polar hydrophobic nature [15,20,24,[30][31][32], assuming that it is unable to penetrate into the water layer adsorbed on the surface of the bonded phase. However, this is a simplified approximation since toluene was found to be more retained in a ZIC-pHILIC column than many other compounds in acetonitrile-water and methanol water MPs [33].…”
Section: Measurement Of Hold-up Volumesmentioning
confidence: 99%
“…This is the case, for instance, of inorganic salts in RPLC. In HILIC these salts cannot be used because of its strong polarity and several studies propose toluene as hold-up volume marker due to its non-polar hydrophobic nature [15,20,24,[30][31][32], assuming that it is unable to penetrate into the water layer adsorbed on the surface of the bonded phase. However, this is a simplified approximation since toluene was found to be more retained in a ZIC-pHILIC column than many other compounds in acetonitrile-water and methanol water MPs [33].…”
Section: Measurement Of Hold-up Volumesmentioning
confidence: 99%
“…As already mentioned in the introduction, compounds such as benzene or toluene are commonly used as HILIC hold-up volume marker [ 5 , 11 , 18 , 40 , 41 , 42 , 43 ]. However, in a previous work it was found that these particular solutes are partially retained and larger solutes of the same type, such as octylbenzene and dodecylbenzene, should be more appropriate hold-up markers [ 24 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The crossed‐linked diol phase (LUNA HILIC column) has been found to be less retentive possibly due to the reduced number of hydroxyl groups on the polymer surface. Other polyhydroxyl phases (YMC PVA‐Sil and Epic HILIC‐HC columns) exhibit stronger retention for polar compounds (Guo, Bhalodia, & Fattal, 2019). The amide group can be found in the chemically bonded amide phase and polyacrylamide phase (TSKgel Amide 80), which are more popular than the diol phase in terms of application.…”
Section: Polar Stationary Phases For Hilicmentioning
confidence: 99%
“…Dinh et al compared the retention of 21 polar stationary phases based on the average retention factors of neutral compounds (α‐hydroxy‐γ‐butyrolactone, cytosine, dimethylformamide, thiocytosine, and uracil) in a mobile phase containing 80% acetonitrile and 25 mM ammonium acetate (Dinh et al, 2011). Guo et al evaluated the retention of 25 polar columns using cytosine as the model compound in the mobile phase containing 85 and 90% acetonitrile and 5 mM ammonium acetate (Guo, Bhalodia, & Fattal, 2019). Both studies find similar ranking of the columns, as shown in Figure 10.…”
Section: Understanding the Hilic Stationary Phasesmentioning
confidence: 99%
See 1 more Smart Citation